DAMPAK COLD SURGE (CS) TERHADAP NET SURFACE HEAT FLUX (NSHF) DI LAUT NATUNA - Agdialta, Rezfiko; Ningsih, Nining Sari; Trilaksono, Nurjanna Joko (Pusat Penelitian dan Pengembangan BMKG, 2024)
Cold Surge (CS) events are often associated with rainfall occurrences in the Jakarta area. However, there is still limited literature on how CS affects other parameters in Indonesia. This study aims to contribute to this literature, particularly regarding the crucial role of CS in the interaction between the ocean and the atmosphere. This research uses the composite difference method to compare changes in Wind Speed (WS), Latent Heat Flux (LHF), Sensible Heat Flux (SHF), Shortwave Radiation (SWR), Longwave Radiation (LWR), and Net Surface Heat Flux (NSHF) during CS phases versus neutral conditions no CS (nCS). The composite difference results indicate an increase in wind speed in the study area, Natuna Sea, with values of 1.17 m/s, 1.45 m/s, and 1.69 m/s for December, January, and February, respectively. This finding explains that the increase in wind speed significantly influences LHF in the negative direction, meaning more LHF is transferred from the ocean to the atmosphere during the CS phase. LHF also predominantly affects NSHF in the study area during the CS period, indicating that more NSHF is leaving the ocean and entering the atmosphere compared to the amount entering the ocean from the atmosphere during the CS phase.